Effectivity of lime leaves (Citrus sp.) in inhibiting Escherichia coli: a meta-analysis - Rohmah, Aenyfatchu; Retnani, Yuli; Jayanegara, Anuraga (Universitas Halu Oleo, 2023)
Antibiotics Growth Promoter (AGP) are currently banned. Citrus leaves have active secondary metabolites that have the potential to be used as phytogenic feed additives. Many in vitro studies have reported the activity of lime leaves against E coli. Therefore, this study aims to integrate various studies in order to obtain comprehensive information on the activity of lime leaves against E coli with a meta-analysis. This research was conducted by collecting studies of citrus leaves from various species, origin, extraction methods, and different antibacterial test methods and comparing the treatment of citrus leaves with controls in inhibiting E coli by looking at the diameter of the inhibition zone. The results showed that kaffir lime leaves as an alternative phytogenic feed additive for AGP were effective in inhibiting E. coli. The inhibitory ability of E. coli bacteria was based on differences in the origin of lime leaves and extraction methods, while differences in levels, types of lime leaves, and antibacterial test methods did not affect the inhibition of E. coli. Citrus leaf extract at a low concentration of 5 mg/ml was able to inhibit E coli bacteria. Keywords: escherichia coli, lime leaf, meta-analysis